Kelayakan Finansial Usaha Budidaya Lebah Madu di KPHL Rinjani Barat, Provinsi Nusa Tenggara Barat - Ni Made Wirastika Sari; Ngakan Agus Trisantika; Andi Iva Mundiyah; Dudi Septiadi (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2020)
Non-timber forest products (NTFPs) is a forest resource that has an important role for the welfare of the communities around the forests, particularly in protected forest areas. Honey is one of NTFPs that have long been used in West Nusa Tenggara province. Increased national honey production is needed to be able to meet the high demand of honey in Indonesia. One of the way to increase production of honey is by doing beekeeping. This study aims to obtain information about the financial feasibility in Protected Forest Management Unit (KPHL) West Rinjani. Sample collection has been done by using purposive sampling method with consideration of the number of holdings stup/the most bee colonies. Research analysis has been done by using a combination of quantitative-qualitative method. Financial analysis conducted to determine the feasibility of beekeeping using investment criteria NPV, BCR and IRR in KPHL Rinjani Barat.The result show that the cultivation of honey bee Apis cerana types in Resort Malimbu feasible with NPV = Rp. 104 229 381 - Rp.1.036.687.824 / 10 years; BCR = 2.85 to 5.79; IRR = 40.92% - 42.34%. Enterprises beekeeping types of Trigona sp in Resort Malimbu also feasible with NPV = Rp. 45,491,153 - Rp. 92,973,767 / 10 years;BCR = 1.21 to 1.34; IRR = 23.52% - 27.91%.